Bioaccumulation of Cadmium and Lead in Prickly Pen Shell in Seribu Archipelago - Etty Riani; Harry Sudrajat Johari; Muhammad Reza Cordova (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Jakarta Bay waters contaminated with heavy metals, so that the waters of the Thousand Islands are also potentially contaminated with heavy metals. The purpose of this study were to determine the condition of the water quality on the Panggang Island and Karya Island, analyze contamination of heavy metals (Cadmium and Lead) in water, sediments and Prickly Pen Shell and then the correlation. Based on Ministry of Environment decree No. 51/2004, water quality in the Panggang Island and Karya Island tend toward to low category. Cadmium and lead concentration in the water on October exceed the quality standards. In the sediment on July and October at Karya Island, concentration of cadmium were exceed the quality standar by RNO. On the other hand, cadmium and lead concentration on Prickly Pen Shell still below standard quality from decree of Director General of POM RI No. 03725. We found highest positive correlation were found between cadmium and lead accumulation in the water and on the Prickly Pen Shell, then positive correlation between cadmium and lead in the water and in the sediment. For the heavy metal contamination, we found contamination of cadmium correlation were higher than lead contamination.